Proposals for effectively regulating the US financial system to avoid yet another meltdown - James Crotty; Gerald Epstein (University of Massachusetts, Department of Economics, 2008)
It is now clear that we are in the midst of the worst financial crisis since the Great Depression. This crisis is the latest phase of the evolution of financial markets under the radical financial deregulation process that began in the late 1970s. This evolution has taken the form of cycles in which deregulation accompanied by rapid financial innovation stimulates powerful financial booms that end in crises. Governments respond to crises with bailouts that allow new expansions to begin. As a result, financial markets have become ever large and financial crises have become more threatening to society, which forces governments to enact ever larger bailouts. This process culminated in the current global financial crisis, which is so deep rooted that even unprecedented interventions by affected governments have thus far failed to contain it. In this paper we first analyze a series of structural flaws in the current financial system that helped bring on the current crisis, and then propose a nine point regulation policy, informed by our analysis, designed to end this destructive dynamic. We believe that if enacted and vigorously enforced, the policy could sharply reduce financial instability and minimize the problems caused by future financial cycles.
Keywords: 330; Finanzmarktkrise; Finanzmarkt; Regulierung; USA